Convex Sets and Subharmonicity of the Inverse Norm Function - Mohammad Taghi Heydari (Abstract and Applied Analysis)
In this paper, we show that in order for a proper compact subset K of plane ℝ2 to be convex, it is necessary and sufficient that inverse norm function be subharmonic.